Manajemen Masjid Kapal Munzalan dalam Pemberdayaan Ekonomi Masyarakat - Wardi, Suhra; Firmansyah, Ferry (Idarotuna, 2025)
This study was conducted with the aim of describing the role of mosque management in improving the community's economy carried out by the Kapal Munzalan Mosque. This study uses descriptive qualitative content analysis methods and library research to develop various programs or policy actions towards solutions to improve the welfare of Muslims in Indonesia starting from Pontianak City. The results of the study indicate that among the programs or policies carried out within the framework of the concept and system of Ziswaf empowerment (Zakat, Infaq and Shadaqoh) are as follows: leading a business from Ziswaf funds, fostering and serving converts and mosque management through service programs, research, training, consultation and networking, Subuh tausiyah through the Munzalan Youtube TV channel and studies on business and entrepreneurship, Sadaqoh Akbar for orphans and conducting scientific research, and establishing Baitulmaal Munzalan Indonesia (BMI) which contributes to poverty alleviation efforts and improving welfare.